Cushing syndrome as the presenting feature of metastatic Leydig cell tumor of the testis - Papadimitris, C.; Alevizaki, M.; Pantazopoulos, D.; Nakopoulou, L.; Athanassiades, P.; Dimopoulos, M.A. (Urology, 2000)
We report a patient with a history of orchiectomy for Leydig cell tumor of the testis who developed Cushing syndrome. This syndrome was due to ectopic production of cortisol and was the primary feature of tumor recurrence. (C) 2000 Elsevier Science Inc.